VAPOR PRESSURES AND EVAPORATION COEFFICIENTS FOR MELTS OF FERROMAGNESIAN CHONDRULE-LIKE COMPOSITIONS - Fedkin A.V.; Grossman L.; Ghiorso M.S. (My University, 2006)
To determine evaporation coefficients for the major gaseous species that evaporate from silicate melts, the Hertz-Knudsen equation was used to model the compositions of residues of chondrule analogs produced by evaporation in vacuum by Hashimoto [Hashimoto A. (1983) Evaporation metamorphism in the early solar nebula-evaporation experiments on the melt FeO-MgO-SiO2-CaO-Al2O3 and chemical fractionations of primitive materials. Geochem. J. 17, 111-145] and Wang et al. [Wang J., Davis A. M., Clayton R. N., Mayeda T. K., Hashimoto A. (2001) Chemical and isotopic fractionation during the evaporation of the FeO-MgO-SiO2-CaO-Al2 O3-TiO2 rare earth element melt system. Geochim. Cosmochim. Acta 65, 479-494], in vacuum and in H2 by Yu et al. [Yu Y., Hewins R. H., Alexander C. M. O’D., Wang J. (2003) Experimental study of evaporation and isotopic mass fractionation of potassium in silicate melts. Geochim. Cosmochim. Acta 67, 773-786], and in H2 by Cohen et al. [Cohen B. A., Hewins R. H., Alexander C. M. O’D. (2004) The formation of chondrules by open-system melting of nebular condensates. Geochim. Cosmochim. Acta 68, 1661-1675]. Vapor pressures were calculated using the thermodynamic model of Ghiorso and Sack [Ghiorso M. S., Sack R. O. (1995) Chemical mass transfer in magmatic processes IV. A revised and internally consistent thermodynamic model for the interpolation and extrapolation of liquid-solid equilibria in magmatic systems at elevated temperatures and pressures. Contrib. Mineral. Petrol. 119, 197-212], except for the late, FeO-free stages of the Wang et al. (2001) and Cohen et al. (2004) experiments, where the CMAS activity model of Berman [Berman R. G. (1983) A thermodynamic model for multicomponent melts, with application to the system CaO-MgO-Al2O3-SiO2. Ph.D. thesis, University of British Columbia] was used. From these vapor pressures, evaporation coefficients (?) were obtained that give the best fits to the time variation of the residue compositions. Evaporation coefficients derived for Fe(g), Mg(g), and SiO(g) from the Hashimoto (1983) experiments are similar to those found by Alexander [Alexander C. M. O’D. (2004) Erratum. Meteoritics Planet. Sci. 39, 163] in his EQR treatment of the same data and also adequately describe the FeO-bearing stages of the Wang et al. (2001) experiments. From the Yu et al. (2003) experiments at 1723 K, ?Na = 0.26 ? 0.05, and ?K = 0.13 ? 0.02 in vacuum, and ?Na = 0.042 ? 0.020, and ?K = 0.017 ? 0.002 in 9 ? 10-5 bar H2. In the FeO-free stages of the Wang et al. (2001) experiments, ?Mg and ?SiO are significantly different from their respective values in the FeO-bearing portions of the same experiments and from the vacuum values obtained at the same temperature by Richter [Richter F. M., Davis A. M., Ebel D. S., Hashimoto A. (2002) Elemental and isotopic fractionation of Type B calcium-, aluminum-rich inclusions: experiments, theoretical considerations, and constraints on their thermal evolution. Geochim. Cosmochim. Acta 66, 521-540] for CMAS compositions much lower in MgO. When corrected for temperature, the values of ?Mg and ?SiO that best describe the FeO-free stages of the Wang et al. (2001) experiments also adequately describe the FeO-free stage of the Cohen et al. (2004) H2 experiments, but ?Fe that best describes the FeO-bearing stage of the latter experiment differs significantly from the temperature-corrected value derived from the Hashimoto (1983) vacuum data. ? 2005 Elsevier Inc. All rights reserved.
Keywords: CHONDRULE; EVAPORATION